Ecossocioeconomias das organizações e (trans)formação ambiental em ecovilas brasileiras - Garrétt, Tatiana Almeida Machado (2020)
In view of the problem situation surrounding the socioecological dynamics put in place, which can be illustrated by the socioeconomic inequalities and climate changes in progress, originated in part by a development style that is based on predominantly urban ways of life, ecovillages are configured as communities associated with certain territories and who experience alternative ways of life in these areas to experience healthier and more sustainable socioecological dynamics. In this thesis, an environmental formation of each of the selected ecovillages was described and evaluated, being these: Inkiri Pirancanga (BA) and Instituto Biorregional do Cerrado (GO), since it was identified both by the bibliographic research and by the bibliometric scientific gaps about: the characterization of ecovillages as Ecosocioeconomies of organizations, the systematic study of the relationship between tourism and education that occurs in ecovillages, the analysis of environmental training programs offered in these communities, and also, an updated overview of ecovillages in Brazil, affiliated by the Global Ecovillages Network. As a result, it was obtained that ecovillages are great real examples of Organizations' Ecosocioeconomies, which in Brazil, despite having only 4 typical ecovillages, these are consolidated in time and in the practices established aiming beyond sustainability, the regeneration of life. Of these 4 ecovillages, 3 present possibilities for the exchange of knowledge and regenerative practices, of which 2 are evaluated in this thesis. Environmental education is classified as ecopedagogy since the development of the planetary citizenship of students and students can be observed based on individual and local reflections and actions. The treated contents were both conceptual, procedural, and attitudinal, reaching the three perspectives of humanity: individual, species and society. Regarding the dynamics of these programs, they were presented in a very horizontal way, both in relation to the community and in relation to students, using the theory-practice-reflection trinity for the construction of knowledge, generally applied. For these reasons, it appears that the researched environmental formations can facilitate teaching and learning as well as influence the transformation of ways of life.